Advancement in the Analysis of Seepage through Cracked Soils - Sugeng Krisnanto; Harianto Rahardjo (Journal of Engineering and Technological Sciences, 2018)
Seepage is an important problem analyzed in geotechnical engineering. Conventionally, the analysis is performed in conditions where the soil is intact. The presence of desiccated cracks requires a seepage analysis that considers not only the soil matrix part of the cracked soil but also the crack network. Currently, there are three approaches in the analysis of seepage through cracked soils: (i) analysis by modeling the cracked soil as an intact material with cracks being represented as macropores; (ii) analysis by modeling the cracked soil as a material with a bimodal pore-size distribution; and (iii) analysis by modeling two components of the cracked soil separately: the soil matrix and the crack network. Each approach is reviewed and discussed in this paper. It was found that each approach is suitable for specific cases: (i) the first method is suitable for seepage analysis of cracked soil deep below the ground surface; (ii) the second method is suitable for seepage analysis of cracked soil at the ground surface under a drying process; (iii) the third method is suitable for seepage analysis of cracked soil at the ground surface experiencing rainwater infiltration. Choosing the appropriate method is essential in modeling the appropriate seepage mechanism.